Effect of Feed Restriction Programs with or without Organic Zinc and Peppermint Leaves Powders on Blood Immunological and Biochemical Indicators and Internal Organs of Broiler Chickens (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was conducted in order to investigate the effect of quantitative and temporal feed restrictions with adding powders of peppermint leaves and organic zinc to the diet for the 2nd and 3rd week on some physiological, immunological and anatomical characteristics of broiler chickens Ross 308 up to 35 days of age. In total, 420 chicks were used, divided into 7 treatments, and each treatment included 3 replicates, with 20 chicks per replicate. The treatments were divided into the control (G1), quantitative feed restriction (40%) only (G2) or with addition of 1% peppermint leaves powder (G3) or with addition of 50 mg/kg of organic zinc powder (G4) and temporal feed restriction (12 hours/ day) only (G5) or with addition of 1% of peppermint leaves powder (G6) or adding 50 mg/kg of organic zinc powder (G7). The results obtained at 21 days of age and as compared with G1 indicated that there was a superiority (p